Prostate-specific antigen density in prostate cancer screening in diabetes mellitus patients - Satır, Atilla; Demirci, Hakan; Ocakoğlu, Gökhan; Erkan, Anıl; Öztürk, Gül Ayşen (The European Research Journal, 2025)
Objectives: The purpose of this study was to examine the function of prostate-specific antigen (PSA) and prostate-specific antigen density (PSAd) in the screening of prostate cancer in individuals with Diabetes Mellitus (DM). Methods: This study was retrospective and cross-sectional. 467 patients who underwent transrectal ultrasound-guided 10-12 core prostate biopsy between 01 January and 31 December 2022 were included. Through the hospital information management system, the demographics, radiological, biochemical, and pathological results of the patients were scanned. Results: PSAd>0.15 ng/mL/cm³ and total PSA (t-PSA)>8.58 ng/mL were substantially associated with an elevated probability of the existence of cancer when all patients were included. PSAd>0.19 ng/mL/cm³ and t-PSA>11.34 ng/mL were shown to be strongly associated with an elevated risk of cancer in patients with DM (P0.14 ng/mL/cm³ and t-PSA>8.49 ng/mL were substantially associated with an elevated probability of cancer presence in individuals without a diagnosis of DM. PSAd>0.15 ng/mL/cm³ and t-PSA>8.58 ng/mL were substantially associated with an elevated probability of cancer presence in individuals with fasting blood glucose (FBG)